Correlation characteristic analysis in diversity multiple‐input multiple‐output radar - Jieyi Liu; Linrang Zhang; Shanshan Zhao; Nan Liu; Juan Zhang (Electronics Letters)
A huge limitation of the correlation analysis in existing scatterer model is that only uniformly distributed scatterers are considered ignoring the variability of scattering intensity in the real situation. In fact, each part of the target has a diverse scattering architecture, thus, the scattering intensity varies with the target surface structure. To make a better equivalent of the real target, the echo correlation coefficient is studied for scattering model which has several variable dominant scatterers to make an equivalent of different scattering architecture in spatial–frequency diversity MIMO radar. The proposed analysis enhances the authenticity of scattering model and expounds the correlation coefficient varying with the scattering intensity and the position of each dominant scatterer. Simulation results are presented to validate the proposed analysis.